Structural, magnetic, optical and electrical characterization of metal manganese oxides with Ni, Zn and Li nanoparticles prepared via thermal treatment method - Ahad, Noorhanim (2018)
Spinel and spinel-like materials are subjects of continuing study in materials science because of their optical, electrical, magnetic, and catalytic properties. These properties are dependent on the chemical composition and microstructural characteristics in which the particle size and shape might be controlled in the fabrication processes. Various fabrication techniques have been reported including chemical, sol-gel, co-precipitation, hydrothermal and microwave. But, most of the present preparation technique of metal manganese oxide nanomaterials are difficult to employ on a larger scale because of their complicated procedures, high reaction temperatures, long reaction times, toxic reagents and contaminated with by products and their potential harm to the environment. In this study the spinel metal manganese oxide nanocrystals were first time synthesized by means of thermal treatment method. This method is cost-effective, environmentally-friendly, has low reaction temperatures, and produced no by-product effluents. An aqueous solution of poly (vinyl pyrrolidone) (PVP) was prepared by dissolving the polymer in deionized water at 90 0C before adding manganese nitrate and the respective metal nitrates for a constant stirring of 2 h. The homogeneous solution was dried at 100 0C for 24 h before grinding and calcined at temperatures ranging from 450 to 850 0C to decompose the organic matters and crystallized the metal manganese oxide nanoparticles. The optimum calcination temperature was confirmed by Fourier transform infrared spectroscopy (FTIR) measurement by the presence of metal oxide bands at all temperatures and the absence of organic bands at 850 0C for NiMn2O4, ZnMn2O4, LiMn2O4 and NiLiMn2O4 nanoparticles. The transmission electron microscopy (TEM) images showed cubical metal manganese oxide nanoparticles that were slightly uniform in both morphology and particle size distribution. The x-ray diffraction (XRD) patterns showed crystalline phases that confirmed the formation of nanocrystalline single-phase spinel metal manganese oxide nanoparticles with a face-centered cubic structure. The average particle sizes were determined from TEM images and it was found that the particle size increased with the calcination temperature from 10.3 to 33.8 nm for NiMn2O4, from 19.8 to 64.4 nm for ZnMn2O4, from 10.2 to 41 nm for LiMn2O4, and from 9.8 to 37.1 nm for NiLiMn2O4. The particle size obtained from TEM images larger than the particle size determined from the XRD data. The magnetic properties were confirmed by the use of electron spin resonance (ESR) spectroscopy, which revealed the existence of unpaired electrons and also measured peak-to-peak line width (ΔHpp), resonant magnetic field (Hr), and the g-factor for NiMn2O4 and LiMn2O4 and NiLiMn2O4 nanoparticles while ZnMn2O4 nanoparticles did not exhibit resonance signal. This could be possibly due to the super exchange interaction that occurs in these nanoparticles. The band gap energy for NiMn2O4, ZnMn2O4, LiMn2O4 and NiLiMn2O4 nanoparticles were determined from UV-vis reflectance spectra using the Kubelka-Munk function and the band gaps were found to decrease with increase in calcination temperature due to particle size increased. The energy band gap values decrease from 1.75 eV to 1.56 eV for NiMn2O4, from 2.43 eV to 1.84 eV for ZnMn2O4, from 2.4 eV to 1.18 eV for LiMn2O4 and decrease from 1.81 eV to 1.75 eV for NiLiMn2O4 when the calcination temperature increases from 450 0C to 850 0C. Electrical conductivities and dielectrics of the sample pellets of NiMn2O4, LiMn2O4 and NiLiMn2O4 nanoparticles were studied through impedance spectroscopy measurements and the calculated value of DC conductivity for the samples calcined at higher temperature, 850 0C are found to be 2.79 x 10-8, 6.17 x 10-8 dan 1.15 x 10-8 Scm-1 for NiMn2O4, LiMn2O4 and NiLiMn2O4 nanoparticles, respectively. The higher particles size was obtained for zinc manganese oxide samples, which are between 19.8-64.4 nm compared to other samples. The energy band gap value for zinc manganese oxide and lithium manganese oxide samples higher than other samples, which are in the range between 1.80-2.43 eV. The lithium manganese oxide samples have higher DC conductivity value, 6.17 x 10-8 S/cm. Thus, this sample would give better performance for electrode. Our results show that zero dimensional spinel NiMn2O4, ZnMn2O4, LiMn2O4 and NiLiMn2O4 nanoparticles have been synthesized using the simple thermal treatment method.